2006
DOI: 10.2139/ssrn.1604078
|View full text |Cite
|
Sign up to set email alerts
|

Agriculture and Nama Negotiations: Searching for the Landing Zone

Abstract: Centad Working Papers are intended to disseminate the preliminary findings of ongoing research both within and outside Centad on issues around trade and development for the purpose of exchanging ideas and catalysing debate. The views, analysis and conclusions are of the author/s only and may not necessarily reflect the views or position of Centad. Readers are encouraged to quote or cite this paper with due acknowledgement to the author and Centad.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2006
2006
2006
2006

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…55 It was observed that if a larger coefficient is used both for developing and developed countries, the tariff rates of developed countries will not be reduced and hence the presence of tariff peak and tariff escalation will not be solved. On the other hand, if a smaller coefficient is used for both groups, the tariff rates of developing countries will come down significantly and will hamper their developmental needs (Ranjan, 2006). So the developing countries stressed on the need to have two different coefficients, a small one for developed countries and a large one for developing countries.…”
Section: Figure 51: a Cross-country Review Of Tariff Binding Scenariomentioning
confidence: 99%
See 2 more Smart Citations
“…55 It was observed that if a larger coefficient is used both for developing and developed countries, the tariff rates of developed countries will not be reduced and hence the presence of tariff peak and tariff escalation will not be solved. On the other hand, if a smaller coefficient is used for both groups, the tariff rates of developing countries will come down significantly and will hamper their developmental needs (Ranjan, 2006). So the developing countries stressed on the need to have two different coefficients, a small one for developed countries and a large one for developing countries.…”
Section: Figure 51: a Cross-country Review Of Tariff Binding Scenariomentioning
confidence: 99%
“…At the Hong Kong Ministerial, the concern over the negotiation on modalities brought several developing countries together to form a core group on NAMA, which was successful in retaining the flexibilities for them (Paragraph 15 of Hong Kong Declaration). The members finally agreed to have a modified 'Swiss formula' for cutting tariff rates (paragraph 14 of the declaration), which creates a possibility of having two different coefficients, one each for developed and developing countries or more than two coefficients (Ranjan, 2006). It has also been decided that the flexibilities to the tariff reduction formula will be a stand-alone provision, i.e., developed countries would not link them with higher reform commitments.…”
Section: Figure 51: a Cross-country Review Of Tariff Binding Scenariomentioning
confidence: 99%
See 1 more Smart Citation